Pemberdayaan Ekonomi Keluarga Melalui Usaha Sapu Lidi Sawit di Desa Buluh Duri - Tria Annisa; Dewita Rohani; Nazwa Rahmayani; Muhammad Fahrizal Hafizh; Adlin Budhiawan (Jurnal Pengabdian Masyarakat, 2025)
Buluh Duri Village, Sipispis District, Serdang Bedagai Regency, North Sumatra, has significant potential for utilizing abundant palm fronds. This potential is utilized by the community, especially housewives, to produce palm frond brooms through a small-scale home industry as an effort to increase family income while processing palm oil waste into economically valuable products. However, studies on the contribution of the palm frond broom business to family economic empowerment are still limited. This community service activity aims to explore the role of the palm frond broom business in improving household welfare, identify the strategies and management patterns implemented, and examine the challenges and opportunities for its development. This study used a descriptive method with a qualitative approach through interviews with five palm frond broom craftsmen, observations of the production process, and documentation during the Community Service Program (KKN). Data analysis was carried out through reduction, presentation, and drawing conclusions. The results show that the palm frond broom business contributes significantly to increasing household income, women’s economic roles, and family and community solidarity. Key strategies include utilizing local raw materials, low initial capital, and marketing through collectors. Challenges faced include limited market access, low selling prices, and a lack of institutional support and product innovation. Training on product innovation, packaging, facilitation of digital market access, and institutional support are needed so that the broomstick business is sustainable and contributes more to the economic empowerment of families in Buluh Duri Village.